Carrie White Avery biography and genealogical records - Avery, Carrie White, 1873-1925.
Genealogical records (4 volumes) from public and family cemeteries in Virginia, Maryland, and District of Columbia, church windows, family Bibles, and private papers. Also includes biography and genealogy of the compiler.
Genealogist and historian.
Collection material in English.
Keywords: Genealogy; Registers of births, etc. -- Maryland; Registers of births, etc. -- Virginia; Registers of births, etc. -- Washington (D.C.); Genealogists; Historians